Kesehatan Mental Mahasiswa dalam Proses Penyusunan Skripsi: Kontribusi Kecerdasan Spiritual dan Daya Juang - Astuti, Fidia; Robingatun, Robingatun (Universitas Trunojoyo Madura, 2025)
Thesis completion is a crucial final stage in undergraduate students' academic journey. During this process, students often face psychological pressure that affects their mental health. This study aims to determine the relationship between spiritual intelligence and adversity quotient with the mental health of final-year students. The research method used is quantitative with a correlational design, and the sampling technique applied was random sampling. The data were analyzed using product moment correlation and multiple linear regression to test both minor and major hypotheses. The results show a correlation coefficient (R) of 0.864. The significance value of F. Change is 0.000, which indicates 0.000 0.05, meaning that spiritual intelligence and adversity quotient are significantly related to mental health. The significance test also shows that the values of F. Change and F. count are greater than F. table, namely 255.581 3.040. These results confirm that the major hypothesis is accepted, and there is a positive relationship between spiritual intelligence and adversity quotient with students' mental health. This finding highlights the importance of strengthening both resilience and spiritual intelligence as part of student support strategies during thesis completion.